2019
DOI: 10.3390/en12132506
|View full text |Cite
|
Sign up to set email alerts
|

CFD Computation of the H-Darrieus Wind Turbine—The Impact of the Rotating Shaft on the Rotor Performance

Abstract: Aerodynamics of the Darrieus wind turbine is an extremely complex issue requiring the use of very advanced numerical methods. Additional structural components of this device, such as, for example, a rotating shaft disturb the flow through the rotor significantly impairing its aerodynamic characteristics. The main purpose of the presented research is to validate the commonly-used unsteady Reynolds averaged Navier–Stokes (URANS) approach with the shear stress transport (SST) k-ω turbulence model based on the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
14
0
1
Order By: Relevance
“…The minimum values of this torque coefficient are about 0.3 after 12 full rotations of the rotor. A similar conclusion was made by Rogowski (2019), who studied the effect of initial conditions by simulating 50 full rotor revolutions. His simulation showed that 15 full revolutions of the rotor was sufficient to obtain repeatable results of both aerodynamic blade loads and velocity profiles behind the rotor.…”
Section: Initial Condition Effectssupporting
confidence: 73%
See 4 more Smart Citations
“…The minimum values of this torque coefficient are about 0.3 after 12 full rotations of the rotor. A similar conclusion was made by Rogowski (2019), who studied the effect of initial conditions by simulating 50 full rotor revolutions. His simulation showed that 15 full revolutions of the rotor was sufficient to obtain repeatable results of both aerodynamic blade loads and velocity profiles behind the rotor.…”
Section: Initial Condition Effectssupporting
confidence: 73%
“…Release 17.1), the length of the time step size should be small enough for the required level of convergence of the solving equations to be obtained in the defined maximum number of iterations per time step. In addition, Rogowski (2019) showed that even if the assumed time step satisfies the desired convergence criterion, it may not be sufficient to capture all aerodynamic phenomena, such as, for example, the effect of the tower's aerodynamic shadow on wind turbine blade loads. Rogowski (2019) and Rezaeiha et al (2019a) agree that for a "clean rotor" (a rotor consisting only of blades) the length of the time step can be assumed equivalent to an azimuth increase, Δθ, of 0.1 deg.…”
Section: Numerical Settingsmentioning
confidence: 99%
See 3 more Smart Citations